Peranan Etika Tutur Bahasa Indonesia Dalam Pembelajaran Di Sekolah - Umar Mansyur (Tamaddun Life, 2017)
Indonesian language learning in schools is directed at improving students’ language skills, bothin the aspects of listening, speaking, reading, and writing. Speaking is one of the language skillsthat is vulnerable in relation to spoken ethics. Language ethics is defined as a normative rule oflanguage use which becomes a general guideline agreed by the language user community thatsuch a method is recognized as a language that is polite, respectful, and in accordance with thevalues that apply in society. Someone who is skilled at speaking must consider what will be saidbefore speaking. It is not wrong if the saying goes that language is someone’s personal mirror.The phrase shows that a person’s personality can be judged by his speech in language. Formany people, good words, gentle, polite, will portray someone as a good person and virtuouscharacter. Conversely, rude and bad words will also cause a bad image in the person. On thatbasis, Indonesian speech ethics has an important role in learning in schools which also contributes to the student’s character education curriculum.